Neuromyelitis optica spectrum disorder and enterovirus-71 infection: A perplexing neurological constellations - Abeer Sabry Safan (14778022) (2023)
Background Neuromyelitis Optica Spectrum Disorder is a span of neuro-inflammatory diseases with observed predilection towards causing optic neuritis, longitudinally extensive transverse myelitis, area postrema syndrome, and diencephalon syndrome. Despite the revolutionizing discovery of its biomarker (Aquaporin-4-IgG-antibodies), its pathogenesis and possible para-infectious immunogenic triggers are rarely reported and not fully understood. Clinical presentation We report a case of Neuromyelitis Optica Spectrum Disorder with positive serum aquaporin-4-IgG-antibodies presenting with severe area postrema syndrome for a month followed by one-week of rapid constellations of extensive brainstem syndrome, transverse myelitis, and left optic neuritis. Magnetic Resonance Imaging of the brain and spine revealed left optic neuritis with multilevel patchy areas of intra-axial high T2- signal of the central and dorsal aspect of the medulla oblongata and cervical-thoracic spinal cord with mild patchy postcontrast enhancement in the lower medulla Interestingly, his illness was preceded by fever and flu-like symptoms and a nasopharyngeal swab polymerase chain reaction was positive for Enterovirus-71. The patient's condition gradually improved with remarkable recovery at nine-week mark. He was treated with plasmapheresis, intravenous pulsed methylprednisolone, an intensive six-week rehabilitation program followed by rituximab. Conclusions Multiple viral infections have been reported to induce Neuromyelitis Optica Spectrum Disorder. To the best of our knowledge, Enterovirus-71 has never been reported to induce this disorder despite its well-reported association with brainstem syndromes and rhombencephalitis. We postulate that this virus has induced immune-cross reactivity that triggered aquaporin-4-IgG-antibodies in our patient which warrants further research. Other Information Published in: Neuroimmunology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nerep.2023.100168